2022
DOI: 10.1101/2022.07.26.501262
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

System-level high-amplitude co-fluctuations

Abstract: Edge time series decompose interregional correlations (functional connectivity; FC) into their time-varying contributions. Previous studies have revealed that brief, high-amplitude, and globally-defined "events" contribute disproportionately to the time-averaged FC pattern. This whole-brain view prioritizes systems that occupy vast neocortical territory, possibly obscuring extremely high-amplitude co-fluctuations that are localized to smaller brain systems. Here, we investigate local events detected at the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…In our partition, some brain areas normally associated with the ventral attention system are co-assigned to nodes of the ventral part of the somatomotor area. Interestingly, previous reports showed co-fluctuations among those regions [42][43][44]. This is an example of how beyond pairwise interactions offer a different angle on how co-activated brain regions could form coherent systems, still grounded in neurophysiology.…”
Section: Redundancy Dominated Systems Of the Human Brainmentioning
confidence: 82%
See 1 more Smart Citation
“…In our partition, some brain areas normally associated with the ventral attention system are co-assigned to nodes of the ventral part of the somatomotor area. Interestingly, previous reports showed co-fluctuations among those regions [42][43][44]. This is an example of how beyond pairwise interactions offer a different angle on how co-activated brain regions could form coherent systems, still grounded in neurophysiology.…”
Section: Redundancy Dominated Systems Of the Human Brainmentioning
confidence: 82%
“…The somatomotor system (SM) splits into modules 2 and 4, and part of it is co-assigned to the ventral attention system (VAN). Interestingly, recent studies highlighted high levels of co-activations between the two [42][43][44]. The default mode network (DMN) and frontoparietal networks (FP) instead are mixed into modules 6 and 7, suggesting that association areas are redistributed when considering higher-order interactions in the community detection process.…”
Section: Relation With the Canonical Systemsmentioning
confidence: 99%
“…Another possibility is signal to noise ratio. In R. F. Betzel, Chumin, Esfahlani, Tanner, and Faskowitz (2022) , the authors studied event structure in different brain systems, for example, default mode, visual, somatomotor, and so forth, including subcortical areas that have poor signal-to-noise ratio relative to neocortex. The authors found that events occurred less frequently in subcortical systems than cortex, supporting the hypothesis that overall signal quality plays a role in event generation.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of representing all possible edges, eTS can be calculated for select subsets. For instance, in a recent paper [ 89 ] the authors extracted eTS for within-system edges [ 90 ] and compared the timing of events across brain systems. Interestingly, event timing was variable across systems and was structured along a sensorimotor–association axis.…”
Section: Edge-centric Networkmentioning
confidence: 99%